Gold Production and the Price Level: The Cassel Three Per Cent Estimate - Phinney, J. T. (Quarterly Journal of Economics, 1933)
I. The Cassel method, 647.— Kitchin's estimate, 648.— II. The problem of the base years: cyclical complications, 649; wholesale vs. general prices, 653; international aspect, 654.— III. The problem of the "normal" gold supply, 655.— IV. The problem of the rate of increase in the demand for gold, 658.— The first sub-assumption, 659; the second, 660; the third, 660.— Bank currency: England, 665; France, 669; Germany, 671; United States, 675.— V. Conclusions, 677.